1998
DOI: 10.1016/s0006-3495(98)74035-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of a Stable Parallel-Stranded DNA Duplex Incorporating Isoguanine:Cytosine and Isocytosine:Guanine Basepairs by Nuclear Magnetic Resonance Spectroscopy

Abstract: Isoguanine (2-hydroxyladenine) is a product of oxidative damage to DNA and has been shown to cause mutation. It is also a potent inducer of parallel-stranded DNA duplex structure. The structure of the parallel-stranded DNA duplex (PS-duplex) 5'-d(TiGiCAiCiGiGAiCT) + 5'-d(ACGTGCCTGA), containing the isoguanine (iG) and 5-methyl-isocytosine (iC) bases, has been determined by NMR refinement. All imino protons associated with the iG:C, G:iC, and A:T (except the two terminal A:T) basepairs are observed at 2 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 51 publications
4
47
0
1
Order By: Relevance
“…All imino protons associated with the 2-oxodA:dC basepairs are consistent with the formation of a stable duplex suggested by T m measurements [18]. 2-oxodA might form stable reverse Watson-Crick basepair with the normal dC [41]. However, the base pairing would not be present in the active site of a DNA polymerase, as the sugar-triphosphate moiety could not fit properly in the active site.…”
Section: Discussionsupporting
confidence: 65%
“…All imino protons associated with the 2-oxodA:dC basepairs are consistent with the formation of a stable duplex suggested by T m measurements [18]. 2-oxodA might form stable reverse Watson-Crick basepair with the normal dC [41]. However, the base pairing would not be present in the active site of a DNA polymerase, as the sugar-triphosphate moiety could not fit properly in the active site.…”
Section: Discussionsupporting
confidence: 65%
“…Similar observations of amino protons of iG and iC in RNA and DNA were reported previously. 27,32 In (GCiGGAiCGCA) 2 , the cross-peaks of iG3 amino-G4H1, iG3H1-G4 amino, iG3H1-G4H1′, iG3H8-G4H8 and typical A-form NOE contacts between C2 and iG3 (Supporting Information Table S1) further indicate formation of Watson-Crick like iGiC base pairs. In (GGiCGAiGCCA) 2 , Watson-Crick like iGiC base pairs are also indicated by cross-peaks of iG6 amino-C7 amino, iG6H1-G2H1, and typical A-form NOE contacts between G2 and iC3 (Supporting Information Table S3).…”
Section: Nmr Assignments and Structural Featuresmentioning
confidence: 98%
“…[13][14][15][17][18][19] The Watson-Crick like iGiC pair, with the amino and carbonyl groups transposed relative to the Watson-Crick GC pair, provides an expanded alphabet [20][21][22][23][24][25][26] for further understanding interactions that shape nucleic acid structure (Figure 1). 7,[25][26][27][28][29][30][31][32] Here, thermodynamic studies of tandem GA pairs flanked by iGiC pairs are reported along with NMR structures of the RNA duplexes (GCiGGAiCGCA) 2 and (GGiCGAiGCCA) 2 . NMR restrained molecular dynamics and energy minimization of (GCiGGAiCGCA) 2 reveal a conformation of tandem sheared GA pairs closed by Watson-Crick like iGiC pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotides containing iG and iC formed a highly stable parallel‐stranded structure. As indicated by NMR spectra, all base pairs interacted by reverse Watson–Crick hydrogen bonds and the structure differed from the canonical B‐DNA form .…”
Section: Parallel Dna and Rna Duplexesmentioning
confidence: 98%